Preliminary Study on Treatment of Palm Oil Mill Effluent (POME) by Sand Filtration-DBD Plasma System - Ariadi Hazmi; Reni Desmiarti; Eka Putra Waldi; Primas Emeraldi (Journal of Engineering and Technological Sciences, 2016)
In the palm oil industry, open ponding, aerobic and anaerobic digestion, physicochemical treatment and membrane ï¬ltration are generally applied as conventional treatments of palm oil mill effluent (POME). In this study, a sand filtration-dielectric barrier discharge (DBD) system was investigated as an alternative process for treating POME. This system can reduce land usage, processing time and costs compared to conventional systems. The removal efficiency of chemical oxygen demand (COD), biological oxygen demand (BOD5), and oil-grease in relation to the applied voltage were studied. Furthermore, the pH and temperature profiles were investigated. The obtained results indicate that the removal efficiency of COD, BOD5, and oil-grease increased with an increase of the applied voltage. The electrical energy consumption needed is about 10.56 kWh/L of POME.